A Practical Two-Stage Frailty Assessment for Older Adults Undergoing Aortic Valve Replacement - Hosler, Quinn P. (J Am Geriatr Soc, 2019)
BACKGROUND: Despite evidence, frailty is not routinely assessed before cardiac surgery. We compared 5 brief frailty tests for predicting poor outcomes after aortic valve replacement and evaluated a strategy of performing comprehensive geriatric assessment (CGA) in screen-positive patients. DESIGN: Prospective cohort study SETTING: A single academic center PARTICIPANTS: Patients undergoing surgical aortic valve replacement (SAVR) (n=91; mean age, 77.8 years) or transcatheter aortic valve replacement (TAVR) (n=137; mean age, 84.5 years) in February 2014-June 2017 MEASUREMENTS: Brief frailty tests (Fatigue, Resistance, Ambulation, Illness, and Loss-of-weight scale; Clinical Frailty Scale; grip strength; gait speed; chair rise) and a deficit-accumulation frailty index based on CGA (CGA-FI) were measured at baseline. A composite of death or functional decline and severe symptoms at 6 months was assessed. RESULTS: The outcome occurred in 8.8% (n=8) after SAVR and 24.8% (n=34) after TAVR. Chair rise test showed the highest discrimination in SAVR (C-statistic=0.76) and TAVR cohorts (C-statistic=0.63). When chair rise test was chosen as a screening test (≥17 seconds for SAVR and ≥23 seconds for TAVR), the incidence of outcome for screen-negative patients, screen-positive patients with CGA-FI≤0.34, and screen-positive patients with CGA-FI>0.34 were 1.9% (n=1/54), 5.3% (n=1/19), and 33.3% (n=6/18) after SAVR, respectively, and 15.0% (n=9/60), 14.3% (n=3/21), and 38.3% (n=22/56) after TAVR, respectively. Compared with routinely performing CGA, targeting CGA to screen-positive patients would result in 54 fewer CGAs, without compromising sensitivity (routine vs targeted: 0.75 vs 0.75; p=1.00) and specificity (0.84 vs 0.86; p=1.00) in SAVR cohort; and 60 fewer CGAs with lower sensitivity (0.82 vs 0.65; p=0.03) and higher specificity (0.50 vs 0.67; p<0.01) in TAVR cohort. CONCLUSIONS: Chair rise test with targeted CGA may be a practical strategy to identify older patients at high risk for mortality and poor recovery after SAVR and TAVR in whom individualized care management should be considered.